A Model for Community Empowerment Based on Islamic Philanthropy - piliyang, riza saharah; Qarni, Waizul; Silalahi, Purnama Ramadani (Dinar : Jurnal Ekonomi dan Keuangan Islam, 2025)
The purpose of this study is to determine the ways in which Islamic philanthropy-based money usage activities contribute to community empowerment. Additionally, describe the paradigm of community empowerment that is being used.This study employed a qualitative research approach. The research is located in Rumah Yatim Medan. Data analysis procedures contain three steps: (1) data reduction, (2) data display, and (3) conclusion drawing or verification. The data for this study was gathered by documentation, interviews, and observation using descriptive qualitative research.The study's findings demonstrate that Rumah Yatim Ar-Rahman Medan's use of Islamic philanthropy-based funding for educational, socioeconomic, da'wah, and productive economy initiatives has been successful and beneficial. Rumah Yatim Ar-Rahman Medan's community empowerment concept has been successfully used in all spheres of education, socioeconomics, da'wah, and the productive economy. However, the productive economy sector should receive greater attention due to its unquestionably sustainable worth.